'Dicho sea de paso' and 'por cierto': two markers of speaker’s exclamative attitude - Adelaida Hermoso Mellado-Damas (Philologia Hispalensis, 2016)
The aim of this article is to propose an analysis of the Spanish adverbs dicho sea de paso and por cierto as discourse markers. Within a polyphonic framework, we shall see in which way the use of dicho sea de paso and por cierto in discourse determines the organization of different points of view convoked by the utterance act. Our interest is to prove that both adverbs present an exclamation framework into which insert the message content.